(untitled) (Altre Modernità, 2015)
Considering food as nourishment as well as a cultural construction, the paper investigates how it can be conceived as an intercultural means of communication among different communities. In particular, in Dahanu Road by Anosh Irani and in Heat and Dust by Ruth Prawer Jhabvala food is a discourse, which is used as an instrument of subjugation or emancipation in Indian-Parsi and Indian–British relations, respectively.